Fundamentals of the elution of gold cyanide from activated carbon - Van der Merwe, Pieter F.(Pieter Francois) (Stellenbosch : Stellenbosch University, 2012)
Dissertation (Ph. D. (Ing.)) -- University of Stellenbosch, 1991.